Notary's Responsibility for Deeds Made With Fake Documents Provided by The Parties - Salis, Lismi; Shallman, Shallman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. In Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary In Article 1 number 1 of the UUJN Notary is a public official who is authorized to make authentic deeds and has other authorities as referred to in this law or based on other laws. A Notary in making a deed sometimes without his knowledge there is false information given by the parties, which then becomes the basis for making an authentic deed. This study aims to analyze and answer the problem regarding the responsibility of a notary for deeds made with false documents provided by the parties in the process of making a notarial deed according to the Notarial Law, and how notarial deeds made based on false documents brought by the person appearing have legal impacts. This study uses the Normative legal research method. Legal materials from primary, secondary, and tertiary legal materials are used as research sources, and the data collected will be analyzed descriptively qualitatively. The results of the study show that notaries are responsible according to the actions they have taken if they are proven to have committed violations in carrying out their duties. They will be responsible in terms of administrative law, civil law or criminal law.Keywords: Notary, Responsibility, Deed